QSARs, Data and Error in the Modern Age of Drug Discovery - Kramer, Christian; Lewis, Richard (Current Topics in Medicinal Chemistry, 2012)
The legacy of the advances made in high-throughput screening (HTS) in the 1990's is a large source of public data from which models can be derived using QSAR methods. This paper will examine the integrity of these public data sources and the implications for model building.
Keywords: error analysis